Implications of Blockchain Deployment in Energy Supply Chain Management: Report Integrity - Al-Madani, Mohammed; Fernando, Yudi; Pua, Wee Sin (Penerbit Universiti Malaysia Pahang, 2022)
The recent strategic deployment of blockchain technology has demonstrated its capacity to provide a ledger platform that can be utilized to secure and effectively manage large scale of data. However, there is little effort to conceptualise the blockchain to facilitate energy supply chain management for report integrity. This study has conceptulized how blockchain technology can solve the challenges of energy supply chain management and energy reports' integrity. Critical review of past literature indicates that blockchain technology offers transparency of energy production and consumption reports. Blockchain keeps all the transactional records and guarantees security, and decentralization between the blockchain network. We have reviewed 121 relevant papers. Through the literature review, this study found blockchain is a suitable option for the integrity of energy reporting in energy supply chain management. It can be concluded that blockchain can help to alleviate the issues of transparency and cost related to energy reporting. This study recommends taking the lead to track energy use and participate in energy reporting using dependable technologies to increase company integrity and efficiency. Decision and policy makers should offer incentives and include regulations on energy reporting requirements.